CATALYSTS OR CONSTRAINTS? DECODING THE INTRICATE LINK BETWEEN FDI AND ECONOMIC GROWTH - Radwayo, Radomir Wojciech; Nowakowski , Karolina Maria; Kowalska , Elzbieta Anna (Economics and Statistics Research Journal (ESRJ), 2024)
This paper undertakes a comprehensive review of the literature concerning the impact of foreign direct investment (FDI) on economic growth. The analysis encompasses both theoretical frameworks and empirical studies, aiming to elucidate the intricate connections between FDI and economic development. While exploring the existing body of knowledge, our focus extends beyond the mere direction of the relationship, delving into the nuanced mechanisms that underlie the association between FDI inflows and sustained economic growth. The theoretical underpinnings examined in this review provide a foundational understanding of the conceptual frameworks shaping discussions on the FDI-economic growth nexus. We scrutinize the diverse theoretical perspectives, ranging from classical economic models to contemporary theories, to distill the core concepts that drive the discourse on how FDI influences economic growth. This exploration serves as a crucial backdrop for the subsequent analysis of empirical evidence. Turning our attention to empirical contributions, this review synthesizes findings from a spectrum of studies that have sought to empirically validate the relationship between FDI and economic growth. By encompassing diverse geographical regions and economic contexts, we aim to capture the breadth and depth of experiences shaping this relationship. The nuanced examination of empirical studies allows us to discern patterns, variations, and potential contingencies that influence the outcomes observed in different settings. Crucially, our review emphasizes the multifaceted nature of the FDIeconomic growth nexus, acknowledging that the relationship is not unidimensional. Instead, it is contingent on various factors, including host country characteristics, institutional frameworks, and industry specific dynamics. By addressing this complexity, we contribute to a more nuanced understanding of the conditions under which FDI acts as a catalyst for economic growth or encounters impediments. In summary, this paper presents a thorough synthesis of the literature on the impact of foreign direct investment on economic growth. By examining both theoretical foundations and empirical evidence, we contribute to a comprehensive understanding of the intricate dynamics governing the relationship between FDI and economic development. This nuanced perspective is instrumental for policymakers, scholars, and practitioners alike, providing valuable insights for informed decision-making in the realm of international economic relations.